Effectiveness of silver diamine fluoride versus sodium fluoride varnish combined with mother's motivational interviewing for arresting early childhood caries: a randomized clinical trial - Randa Yassin; Hala Amer; Maha El Tantawi (BMC, 2023)
Abstract Background Silver Diamine Fluoride (SDF) has gained attention as one of the minimally invasive modalities to manage ECC although it causes black staining of treated carious lesions. A possible affordable alternative may be Sodium Fluoride (NaF) varnish combined with good oral hygiene promoted by parental Motivational Interviewing (MI). The study compared the effectiveness of 38% SDF solution and 5% NaF varnish supported by parental MI in arresting ECC. Materials and methods Children aged ≤ 4 years old with at least one active carious lesion (ICDAS score ≥ 3) were randomly assigned to treatment by a single application of 38% SDF solution or a single application of 5% NaF varnish supported by two MI sessions for mothers at baseline and after three months. Chi-Squared test was used to compare groups and multilevel logistic regression analysis was used to assess the effect of the interventions on ECC arrest adjusting for confounders. The interaction between the type of intervention and baseline lesion severity, moderate (ICDAS 3/4) or advanced (ICDAS 5/6), was also assessed. Results The study included 165 children with 949 active lesions. After 6 months, there were no significant differences between SDF and NaF/MI groups in overall caries arrest (63.7% and 58.1%, p = 0.08), and in moderate lesions (72.9% and 69.6%, p = 0.52). However, in advanced lesions, the arrest rate was significantly higher in the SDF than the NaF/ MI group (60.3% and 50.0%, P = 0.01). Multilevel multiple logistic regression showed no significant differences between the interventions (AOR = 1.56, P = 0.27) with significant interaction between the intervention and baseline lesion severity (p < 0.001). Moderate lesions treated with SDF (AOR = 3.69, P = 0.008) or NaF/MI (AOR = 3.32, P < 0.001) had significantly higher odds of arrest than advanced lesions treated with NaF/ MI with no difference between advanced lesions treated with SDF or NaF/ MI (AOR = 1.85, P = 0.155) in arrest rate. Conclusion NaF/ MI can be an alternative to SDF in arresting advanced and moderate ECC lesions without staining with stronger effect on moderate lesions (ICDAS 3/4). Trial registration The trial was retrospectively registered at clinicaltrial.gov registry (#NCT05761041) on 9/3/2023.